Connecting development of pragmatic competence with the CEFR - Kusevska, Marija (Linguistica (Ljubljana), 2014)
The aim of this paper is to look at how The Common European Framework of Reference for Languages (CEFR) can facilitate research of pragmatic competence development. Central to developing pragmatic competence are the language functions (or speech acts) and the conventions of politeness. In particular, we focus on how Macedonian learners of English at B2 level express their disagreement, and we put their performance in relation to the functions and the politeness maxims postulated in Vantage (van Ek/Trim 2001) and the Common European Framework of Reference for Languages (2001). Data for the analysis was compiled by means of a Discourse Completion Task (DCT) consisting of nine tasks which required the students to express an opposing view to the one given in the tasks. In our analysis, we classified disagreement as strong, weak, direct and hints. We focus on the linguistic means that learners used to express and to modify their disagreement. In particular, we discuss the use of lexical and syntactic modifiers, putting more emphasis on the use of modal verbs and I think. We end the paper with a conclusion that the CEFR and the accompanying books provide a valuable tool not only because they list the exponents of the functions, but also because they explain the principles that these exponents are motivated by. Finally, we raise two issues that we believe are important for further consideration. One is development of further research across all levels with the aim of better understanding the processes governing the acquisition of pragmatic competence. The other is developing research on what teaching methods and techniques should be employed to facilitate it.
Keywords: actes de langage; anglais; angleščina; Cadre européen commun de référence pour les langues; CECRL; compétence pragmatique; English; étudiants macédoniens; jezikovna dejanja; makedonski študenti; pragmatična kompetenca; SEJO; Skupni evropski jezikovni okvir; tuji jeziki